COVID 19 PANDEMIC SHIFTING THE JOB SATISFACTION LANDSCAPE AMONG EMPLOYEES - Takupiwa Nyanga; Andrew Chindanya (Business Excellence and Management, 2020)
The purpose of this study was to analyze the implication of COVID 19 on job satisfaction among workers in SMEs in Zimbabwe. A purely qualitative study was undertaken to establish how COVID 19 affects the attitude of workers towards their work. The study utilized a multiple case study design with an interview being utilized as the main data collection tool. Data was collected from a sample of 20 (n=20) participants who were selected using purpose sampling approach. Data was analyzed using a combination of thematic analysis and descriptive analysis. The study found out that COVID 19 significantly affects job satisfaction among workers in SMEs. COVID 19 resulted in the decrease in workers’ salaries, employment opportunities and job security. The study also found out that COVID 19 increases employee stress due to fear of contracting the disease and propel poor working conditions for workers in SMEs. It was therefore recommended that employers should lay special emphasis on ways and strategies that protect workers from contracting COVID 19. The measures and strategies which can be used to promote employee satisfaction during the COVID 19 pandemic include among others giving workers risk allowances, creating a safe work environment, provide personal protective equipment to workers and employing flexible work arrangement